2006
DOI: 10.1021/pr0504788
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Cerebrospinal Fluid Proteome in Multiple Sclerosis:  Characterization by Ultrafiltration, Liquid Chromatography, and Mass Spectrometry

Abstract: Neurological diseases, including multiple sclerosis (M.S.), often provoke changes in the functioning of the endothelial and epithelial brain barriers and give rise to disease-associated alterations of the cerebrospinal fluid (CSF) proteome. In the present study, pooled and ultrafiltered CSF of M.S. and non-M.S. patients were digested with trypsin and analyzed by off-line strong cation exchange chromatography (SCX) coupled to on-line reversed-phase LC-ESI-MS/MS. In an alternative approach, the trypsin-treated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 84 publications
3
63
0
Order By: Relevance
“…Endogenous regulators modulate these two protease pathways as endogenous peptide inhibitors, activators, and in vivo secretory vesicle proteins. Neuropeptides in CSF (cerebrospinal fluid) in neurological diseases can monitor brain nervous activity since neuropeptides represent active neurotransmission (129,130).…”
Section: Future Perspectives -Linking Neuropeptide Mechanisms For Tramentioning
confidence: 99%
“…Endogenous regulators modulate these two protease pathways as endogenous peptide inhibitors, activators, and in vivo secretory vesicle proteins. Neuropeptides in CSF (cerebrospinal fluid) in neurological diseases can monitor brain nervous activity since neuropeptides represent active neurotransmission (129,130).…”
Section: Future Perspectives -Linking Neuropeptide Mechanisms For Tramentioning
confidence: 99%
“…Standardized sample handling is also important when trying to compare results between different laboratories (12)(13)(14). In the search for molecular biomarkers related to disorders of the central nervous system, CSF is the most promising biofluid because of its close contact to the affected tissue (13,(15)(16)(17)(18)(19)(20).…”
Section: © 2011 American Association For Clinical Chemistrymentioning
confidence: 99%
“…To address these issues, a number of studies have applied a variety of novel proteomic approaches to the global analysis of biological fluids obtained from affected individuals including plasma and especially CSF. The overall goals of such studies were to create a databank of proteins found in the CSF of multiple sclerosis patients [43] and identify proteins that are uniquely detected in multiple sclerosis as compared to controls [28,44]. However, the search for unique disease markers by the analysis of the CSF presents multiple challenges.…”
Section: Challenges In the Proteomic Analysis Of The Csf From Multiplmentioning
confidence: 99%
“…A number of studies have used proteomic approaches in order to define the protein composition or identify differentially expressed proteins in the CSF of multiple sclerosis patients [28,43,44]. One of the investigations by 2-DE and MS compared CSF obtained from three multiple sclerosis patients with that of three individuals affected by other inflammatory conditions, two with CNS sarcoid and one with viral meningitis [28].…”
Section: Proteomic Analysis Of the Csf Obtained From Multiple Sclerosmentioning
confidence: 99%
See 1 more Smart Citation